2010 International Conference on Intelligent Networking and Collaborative Systems 2010
DOI: 10.1109/incos.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

Using Bi-clustering Algorithm for Analyzing Online Users Activity in a Virtual Campus

Abstract: Data mining algorithms have been proved to be useful for the processing of large data sets in order to extract relevant information and knowledge. Such algorithms are also important for analyzing data collected from the users' activity users. One family of such data analysis is that of mining of log files of online applications that register the actions of online users during long periods of time. A relevant objective in this case is to study the behavior of online users and feedback the design processes of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…In our future work, we would like to compare the results of the data mining methods employed in this work with that of a bi-clustering algorithm initially studied in [23]. This approach is also useful to extract relevant knowledge about user activity for other purposes beyond navigation patterns, such as identifying activities performed by students as well as to study time parameters related to such activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our future work, we would like to compare the results of the data mining methods employed in this work with that of a bi-clustering algorithm initially studied in [23]. This approach is also useful to extract relevant knowledge about user activity for other purposes beyond navigation patterns, such as identifying activities performed by students as well as to study time parameters related to such activities.…”
Section: Discussionmentioning
confidence: 99%
“…not for real learning needs). Yet, the lack of sufficient computational resources is the main obstacle to process large amounts of data in real time and hence in real situations this processing tends to be done off-line in order to avoid harming the performance of the logging application, but as it takes place after the completion of the learning activity has less impact on it [6,23].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, |S k | denotes the cardinality of S k , i.e., the number of samples in bi-cluster Given a data matrix A, the bi-clustering problem is to design algorithms to find bi-clusters B {B k : k 1, 2, /, K} of it, i.e., a sub-set of matrices of A such that samples (rows S k ) of each bicluster B k exhibit some similar behavior under the corresponding features (columns, F k ). In other words, the bi-clustering problem is to identify a set of bi-clusters B k =(S k , F k ) such that each bicluster B k satisfies some specific characteristics of homogeneity (Xhafa et al, 2011).…”
Section: Bi-clustering: Definitions and Problem Formulationmentioning
confidence: 99%
“…Adopting other datamining techniques, the authors of [28] proposed the use of a biclustering algorithm to extract information from the daily online activities of virtual campus users. The results showed that the knowledge extracted from log files with statistical measures helped to provide better usability and adaption to user preferences.…”
Section: Evaluation Factors and Artificial Intelligencementioning
confidence: 99%